2018
DOI: 10.1007/s00438-017-1414-1
|View full text |Cite
|
Sign up to set email alerts
|

Identifying potentially common genes between dyslipidemia and osteoporosis using novel analytical approaches

Abstract: Dyslipidemia (DL) is closely related to osteoporosis (OP), while the exact common genetic mechanisms are still largely unknown. We proposed to use novel genetic analysis methods with pleiotropic information to identify potentially novel and/or common genes for the potential shared pathogenesis associated with OP and/or DL. We assessed the pleiotropy between plasma lipid (PL) and femoral neck bone mineral density (FNK BMD). We jointly applied the conditional false discovery rate (cFDR) method and the genetic an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 53 publications
1
8
0
Order By: Relevance
“…Among adults, a small male predominance of HPI-related outcomes has been found in a meta-analysis based on 169 studies (OR 1.12, 95% CI: 1.09, 1.15) [ 407 ]. Shared genetic basis underlying OP and a variety of HPI-related chronic extra-gastroduodenal diseases (CAD, DM, dyslipidemia) has been reported [ 408 , 409 , 410 , 411 , 412 , 413 , 414 , 415 , 416 , 417 , 418 , 419 ]. The shared biology and bi-(multi-)directional links between OP and HPI-associated chronic diseases apply particularly to CVD, CKD, CLD, DM and neurodegenerative diseases; these disorders are interrelated and often accompanied by OP/OF [ 420 , 421 , 422 , 423 , 424 , 425 , 426 , 427 , 428 , 429 , 430 ], and the risk of OP/OF increases when two or more HPI-associated chronic diseases are present.…”
Section: Hpi-associated Chronic Extra-gastroduodenal Diseases Medmentioning
confidence: 99%
“…Among adults, a small male predominance of HPI-related outcomes has been found in a meta-analysis based on 169 studies (OR 1.12, 95% CI: 1.09, 1.15) [ 407 ]. Shared genetic basis underlying OP and a variety of HPI-related chronic extra-gastroduodenal diseases (CAD, DM, dyslipidemia) has been reported [ 408 , 409 , 410 , 411 , 412 , 413 , 414 , 415 , 416 , 417 , 418 , 419 ]. The shared biology and bi-(multi-)directional links between OP and HPI-associated chronic diseases apply particularly to CVD, CKD, CLD, DM and neurodegenerative diseases; these disorders are interrelated and often accompanied by OP/OF [ 420 , 421 , 422 , 423 , 424 , 425 , 426 , 427 , 428 , 429 , 430 ], and the risk of OP/OF increases when two or more HPI-associated chronic diseases are present.…”
Section: Hpi-associated Chronic Extra-gastroduodenal Diseases Medmentioning
confidence: 99%
“…Bone mineral density (BMD) and serum total cholesterol (TC) are among two of the most extensively studied clinically-oriented phenotypes, associated with the two of the most common polygenic age-related pathologies, osteoporosis (OP) and cardiovascular disease (CVD). There is an abundant literature showing correlation between these biomarkers and possible mechanisms underlying it [14], although the views and the data remain controversial [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, it is unclear whether BMD and lipids are related due to pleiotropic genetic influences or through direct causal influence of one on the other. One of the most convincing studies employed conditional false-discovery rate and other approaches on large genome-wide association studies (GWAS) of BMD and cholesterol and found pleiotropy among the significant single nucleotide polymorphisms (SNPs) for the two phenotypes [4]. A comprehensive GWAS in a combined sample of the TwinsUK study and the Cooperative Health Research in the Region of Augsburg (KORA) study including nearly 8000 individuals identified 145 SNP associations with over 400 blood metabolites [7].…”
Section: Introductionmentioning
confidence: 99%
“…First, two GWAS datasets were combined and 8,285,296 common SNPs with summary statistics remained for both CAD and BW phenotypes. Then, we performed LD-based pruning (r 2 ≤ 0.2) using HapMap III genotypes as a reference, and the SNP of the pair with longer allele frequency was retained [ 31 , 68 ]. After merging and pruning, 141,779 variants were prepared for further analysis.…”
Section: Methodsmentioning
confidence: 99%